To solve the radical equation \( \sqrt{5x + 5} - x = 1 \), we will first isolate the square root and then square both sides.
Here are the steps:
- Isolate the square root:
\[ \sqrt{5x + 5} = x + 1 \]
- Square both sides:
\[ 5x + 5 = (x + 1)^2 \]
- Expand the right side:
\[ 5x + 5 = x^2 + 2x + 1 \]
- Rearrange the equation:
\[ 0 = x^2 + 2x + 1 - 5x - 5 \]
\[ 0 = x^2 - 3x - 4 \]
- Factor the quadratic:
\[ 0 = (x - 4)(x + 1) \]
- Set each factor to zero:
\[ x - 4 = 0 \quad \Rightarrow \quad x = 4 \] \[ x + 1 = 0 \quad \Rightarrow \quad x = -1 \]
So, the potential solutions are \( x = 4 \) and \( x = -1 \).
- Verify both solutions in the original equation:
-
For \( x = 4 \): \[ \sqrt{5(4) + 5} - 4 = \sqrt{20 + 5} - 4 = \sqrt{25} - 4 = 5 - 4 = 1 \quad \text{(valid)} \]
-
For \( x = -1 \): \[ \sqrt{5(-1) + 5} - (-1) = \sqrt{-5 + 5} + 1 = \sqrt{0} + 1 = 0 + 1 = 1 \quad \text{(valid)} \]
Both solutions satisfy the original equation.
Thus, the solutions are \( x = 4 \) and \( x = -1 \).
The correct response is: x equals 4 and x equals negative 1.